The Intervening Effect of Interpersonal Trust on The Relationship Between Multiple Measured-Based Performanced Evaluation and Job-Related Tension - Siti Fathonah; Mahfud Sholihin (The Indonesian Journal of Accounting Research, 2013)
This study examines the effect of the use of multiple performance measures (a combination of financial and non-financial measures) in performance evaluations on subordinates’ job-related tension. Specifically, this study investigates whether the effect of such measures is indirect through interpersonal trust. This study hypothesizes that the relationship between multiple measures-based performance evaluation and subordinates’ job-related tension is indirect through subordinates’ interpersonal trust towards their superiors. The results, based on a sample of 70 managers, support the expectation that the use of a mix of financial and non-financial measures in performance evaluations has no direct effect on subordinates’ job-related tension.  Instead, the effect of such a mix of performance measures on subordinates’ job-related tension is indirect through interpersonal trust.